The Learning of Arabic Speaking Skills With Constructive Theory Perspective - Elok Rufaiqoh; Abdul Wahab Rosyidi; Umi Machmudah; Nahla Ibrahim El Jack Ibrahim; Achmad Ja'far Sodik (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
The purpose of this research was to find out the concrete form of Arabic speaking skills learning with the perspective of constructivism theory at Institut Agama Islam Al-Qodiri Jember (IAI Al-Qodiri Jember), how the class setting, the learning process, and the products produced by students after learning. This study used a descriptive qualitative approach. Data collection techniques used observation and interviews. The data analysis used in this research is Miles and Huberman's data analysis theory, which includes: data collection, data simplification, data presentation, and conclusion. The results of this study concluded that: first, the class setting in Arabic speaking skills learning with the perspective of constructivism theory by the way the lecturer arranges the chairs in the class into groups. So, students can interact actively by practicing Arabic communication. Second, the process of learning Arabic speaking skill with a constructivist approach consists of three stages, namely planning, implementation, and evaluation, all of which focus on constructivist learning by paying attention to the principles contained therein. Third, the product produced by students in this lecture is a language conversation video as a concrete form of the construct results of students' thoughts about the Arabic conversation concepts they make. The process of learning Arabic speaking skills through the methods above can make students master 21st-century skills including creative thinking, communication, and collaboration.